WATER RESOURCES ENGINEERING DESIGN OF LAKE RESORT JATILUHUR RESERVOIR - ADYATMA WIDYAMARTHA, KADEK
Lake Resort Jatiluhur Reservoir is an integrated tourism area project in the form of a resort that will be built on the edge of the Jatiluhur Reservoir area. Lake Resort Jatiluhur Reservoir provides a variety of facilities that can be used by visitors, ranging from restaurants, spa areas, swimming pools to lodging areas. There are several structures that are planned to be built on the waters of the Jatiluhur Reservoir, therefore it is necessary to determine the designed water elevation level to estimate the safe height of the structure from the reservoir surface water level. In addition, in planning a building, the design of the regional drainage system is also an important aspect. Rainwater that falls on the resort area must be drained properly so there is no excessive inundation and runoff. Determination of the designed water elevation level is based on hydrological and sedimentation analysis. The hydrological analysis consists of determining the designed flood discharge and the routing process that will result in the designed flood water elevation. Meanwhile, the analysis of erosion-sedimentation use the USLE method to estimate the increase in reservoir bottom elevation due to sedimentation. The design scope of the drainage system is limited to the drainage of the Lake Resort area based on rainwater runoff. Drainage design is done by dividing the land into several catchment areas to create a drainage scheme and calculating rain run-off using rational method. Furthermore, the dimensions of the drainage channel components are carried out as needed.